Pengaruh Latihan Foam Roller Terhadap Penurunan Efek Delayed Onset Muscle Soreness(DOMS) Otot Quadriceps Pada Pelari Marathon Di Persatuan Indorunner Surabaya - Prianto, Benidektus Adi, Dwi Rosella Komala Sari, S.Fis., M.Fis (2016)
Background : Quadriceps muscle is the muscle that works in eccentric patterns in a run and also serves as a shock absorber. Delayed Onset Muscle soreness(Doms) is a icroscopic damage to the muscle fibers due to a continuous exercise in a long time as eccentric exercise. Foam roller serves as a tubular tool for self-massage and useful for muscle relaxation. The objective of research : To determine the effect of foam roller exercises to decrease muscle quadriceps doms effect on marathon runners in unity indorunner surabaya. The benefit of research : Provide scientific information regarding the presence or absence of the influence of foam roller exercises to decrease muscle quadriceps Doms effect on marathon runners in unity indorunner Surabaya. The method of research : This type of research is pre-experimental with pre-test and post test one group design. Result of the research : Based on the statistical test result after 72 hours p value is 0.004, which means p-value <0.05 so that Ho refused and Ha accepted. Conclusion : There effect of foam roller exercises to decrease doms effect such as pain in marathon runners in unity indorunner surabaya